Transplantation, Legal Adoption, Harmonization of OMNIBUS LAW and Investment Law - Syprianus Aristeus (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
The best way in an effort to manage investment is by transplanting, adopting laws, harmonization by making breakthroughs to existing regulations, such as in the case of implementing the Job Creation Law. The Omnibus Law offered by the government as a “practical and pragmatic” solution is a political and legal policy to cut various regulatory barriers, to simplify bureaucracy, to accelerate services, to increase efficiency, to increase competitiveness, and to prevent opportunities for corrupt behavior. The government must evaluate this law (Job Creation) where there is still overlap without regard to regulations. The statement of the problem in this scientific paper is why there is a conflict of interest and regulations that are not in accordance with the laws and regulations? As normative juridical research, this research is based on an analysis of legal norms. The Omnibus Law is a political product. In the process of its discussion, the law resulted from a political process. The government must evaluate this law (Job Creation) where in the process of making it there is still overlap without regard to regulations.